Large Vestibular Aqueduct Syndrome: Parents’ and Audiologists’ Perspectives - Sullivan, James Connor; Johnson, Carole E.; Danhauer, Jeffrey L.; Jilla, Anna Marie; Sanchez, Kristin R. (Journal of the American Academy of Audiology, 2019)
Large vestibular aqueduct syndrome (LVAS) is an auditory disorder that is difficult to diagnose and manage; it is confirmed when the vestibular aqueduct is >1.5 mm in diameter. Diagnosis of LVAS in children can devastate parents and challenge healthcare professionals who serve these patients and their families.This study surveyed parents of children with LVAS about their knowledge of and experiences with LVAS and their attitudes about the support provided to them by healthcare professionals. This study also surveyed audiologists about their knowledge of and experiences with LVAS and their level of confidence in serving families with children having this disorder.Cross-sectional survey.100 parents, mostly mothers, and 144 audiologists responded to invitations to participate in surveys designed to elicit information about their knowledge of, experiences with, and attitudes toward LVAS.Invitations via links to participate in a survey on surveymonkey.com were posted in LVAS support group pages on Facebook.com for parents and sent to audiologists randomly selected from the American Academy of Audiology Membership Directory. Descriptive statistics were used to analyze trends in parents’ and audiologists’ responses.A response rate could not be obtained for the parents’ survey because it was impossible to know how many parents actually viewed the invitation to participate via Facebook.com. The response rate for the audiologists’ survey was 10%. Most of the parents reported that their children had clinical trajectories similar to those of cases reported in the literature, and said they needed more information from their healthcare providers, especially pediatricians and primary care physicians. Most of the audiologists felt confident in their knowledge of and/or skills in aiding in the diagnosis and/or treatment of LVAS, except for issues surrounding cochlear implants. Audiologists were interested in obtaining continuing education about LVAS from multiple sources.Parents of children having LVAS need greater support from their healthcare providers, who in turn need additional information on the topic and should collaborate for supportive and appropriate interprofessional care.
Keywords: audiologists; children; cochlear implants; counseling; large vestibular aqueduct syndrome; parents; physicians; sensorineural hearing loss